(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Many development projects set up by the Government of Independent India in the past to improve the economic condition people in backward mineral rich regions, went against the interest of poor tribal and ecosystem people. It has been revealed from various research studies that exploitation of mineral resources and promotion of mineral-based industries in tribal areas ruined their sustainable means of subsistence. The did not get any opportunity to switch over from their traditional land and forest-based living to modern industries and mechanized mines, as they did not have minimum level of modern education to acquire modern skills. This has resulted in massive displacement of tribal people from their hearth and home. About 40 per cent of them have been displaced from all over the country by the development projects like river dam, irrigation projects, mines, industries, etc., although they constitute only about 8.6% per cent of the total population of India. In the light of this, I being a tribal student and victim of mineral-based industrial development plans to do my doctoral level research on mineral-based industries and their impact on tribals. The area of my study is northern plateau region of Odisha comprising three mineral rich tribal districts namely, Sundargarh, Keonjhar and Mayurbhanj districts.